2021
DOI: 10.12681/jhvms.28486
|View full text |Cite
|
Sign up to set email alerts
|

A New Outbreak in Sea Bass Farming in Turkey: Aeromonas veronii

Abstract: Turkey produces most of the European sea bassin Europe and bacterial diseases are the main cause of economic loss during the production cycle. This research presents the first extended study of the Aeromonas veronii infection in sea bass on the Turkish coast of the Aegean Sea. An outbreak was observed in three different sea bass farms and diseased fish with clinical symptoms were sampled. Abdominal distention, hemorrhages on the body and anus, enlarged spleen and liver, and hemorrhages in the internal organs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…In the present study, the LD 50 of A. veronii in D. labrax fingerlings was (>1 × 10 8 to 6.2 × 10 7 ) CFU fish −1 ; this value was higher than the value recorded by (Smyrli et al, 2017(Smyrli et al, , 2019Wang et al, 2021) was 10 5 , 4.2-8.5 × 10 5 and 1.4-2.4 × 10 6 , respectively, while it was nearly similar to the LD 50 estimated by Tanrıkul and Dincturk (2021) which was 0.85-1.28 × 10 8 , variation in the LD 50 is attributed mainly to the difference in virulence and pathogenicity of challenging isolates. LD 50 of A. caviae in D. labrax ranged between 2.9 and 8.3 × 10 7 CFU.…”
Section: Ta B L E 4 Virulence Genes Profile Of the Recovered Aeromona...supporting
confidence: 76%
See 2 more Smart Citations
“…In the present study, the LD 50 of A. veronii in D. labrax fingerlings was (>1 × 10 8 to 6.2 × 10 7 ) CFU fish −1 ; this value was higher than the value recorded by (Smyrli et al, 2017(Smyrli et al, , 2019Wang et al, 2021) was 10 5 , 4.2-8.5 × 10 5 and 1.4-2.4 × 10 6 , respectively, while it was nearly similar to the LD 50 estimated by Tanrıkul and Dincturk (2021) which was 0.85-1.28 × 10 8 , variation in the LD 50 is attributed mainly to the difference in virulence and pathogenicity of challenging isolates. LD 50 of A. caviae in D. labrax ranged between 2.9 and 8.3 × 10 7 CFU.…”
Section: Ta B L E 4 Virulence Genes Profile Of the Recovered Aeromona...supporting
confidence: 76%
“…Our results revealed the presence of haemorrhagic skin lesions, exophthalmia, cataracts, congested liver, spleen and posterior kidney. Accordingly (Smyrli et al., 2017, 2019; Tanrıkul & Dincturk, 2021; Wang et al., 2021) have described identical clinical signs and post‐mortem lesions in naturally and experimentally infected D. labrax . Similar findings were also mentioned by Azzam‐Sayuti et al.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Meanwhile, A. veronii infection is less abundant in cultured marine fishes as it was reported only from diseased European seabass (Smyrli et al, 2019;Tanrıkul and Dincturk, 2021). To the best of our knowledge, this is the first record of A. caviae isolation from diseased seabass or even from any diseased marine fish species, A. caviae has previously been isolated from diseased freshwater fishes as Rhamdia quelen (Baldissera et al, 2018), Oreochromis niloticus (Roy et al, 2018), Clarias gariepinus (Mulia et al, 2020), red hybrid tilapia (Azzam-Sayuti et al, 2021) and Pelteobagrus fulvidraco (Zhai et al, 2021).…”
Section: Effect Of Bacterial Virulence Genes On the Activity Of Antio...mentioning
confidence: 81%
“…1 and 2). European seabass infected with S. putrefaciens and A. hydrophila revealed epidermal lesions progressively extended to musculature (muscle ulceration), hemorrhagic caudal fins, fin rot, red inflamed vents and abdominal distension (Korun et al, 2009;Smyrli et al, 2017;Tansel Tanrikul and Dinçtürk, 2021). Similar clinical signs have been previously reported in rabbitfish, Siganus rivulatus (Saeed et al, 1987) The phenotypic characterization of bacterial isolates demonstrated that five isolates had phenotypic characteristics corresponded to Shewanella putrefaciens and three isolates had phenotypic characteristics corresponded to Aeromonas species (Table 1).…”
Section: Discussionmentioning
confidence: 99%